Identifikasi Senyawa Antijamur dari Agens Hayati Rizoplan - KEZIA, KEZIA; KHALIMI, KHAMDAN; PHABIOLA, TRISNA AGUNG (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.10, No.4, Oktober 2021, 2021)
Identification of Antifungal Compounds From Biological Agents of Rhizoplan Fusarium wilt disease that attacks plants is caused by Fusarium oxysporum , this disease can cause significant losses to plants. The use of rhizoplan bacteria is considered as an alternative to control fungal growth. The use of selective and environmentally friendly rhizoplan bacterial control. The purpose of this study was to identify antifungal compounds in bacterial rhizoplans. The results showed that rhizoplan bacteria were able to inhibit the growth of F. oxysporum f.sp. lycopersici fungal colonies on potato dextrose agar (PDA) media with an inhibition percentage of 88.24% when compared to the control. The results of the filtrate test of rhizoplan bacteria at a concentration of 50% were able to inhibit the growth of F. oxysporum f.sp. lycopersici with an inhibition percentage of 90.14%. The antifungal compounds produced by rhizoplan bacteria isolate RbJN10 on Gas Chromatography Mass Spectrometry (GC-MS) analysis were Dihydro-3- (2H)-thiophenone; 2(5H)- Furanon; 2(3H)- Furanone,5-methyl; 2- Furancarboxaldehyde, 5-methyl; 2,5Dimethylfuran-3,4(2H, 5H)-dione; 2- Furancarboxylic Acid; Methyl 2-furoate; 1,2-Ethanadiol,1-(2-furanyl)-; 5- hydroxymethylfurfural.